Applied medical image processing : a basic course - Birkfellner, Wolfgang (Boca Raton, FL. : CRC Press, 2011)
'Given the rapid evolution of radiological imaging in the past four decades, medical image processing nowadays is an essential tool for clinical research. Applications range from research in neuroscience, biomechanics and biomedical engineering to clinical routine tasks such as the visualization of huge datasets provided by modern computed tomography systems in radiology, the manufacturing of patient-specific prostheses for orthopedic surgery, the precise planning of dose distributions in radiation oncology, the fusion of multimodal image data for therapymonitoring in internal medicine, and computer-aided neurosurgical interventions'--Provided by publisher.
Book is accompanied by 1 computer optical disc, entitled'Applied medical image processing : a basic course' bearing the same call number and available at Bahagian Koleksi Media and Makmal Digital, Perpustakaan Dr. Abdul Latiff, KKL.
Includes bibliographical references and index.
Keywords: Diagnostic imaging